2005
DOI: 10.4489/myco.2005.33.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Infection Structures after Inoculation withColletotrichum orbiculareon the Leaves of Cucumber Plants Pre-inoculated with Two Bacterial StrainsPseudomonas putidaorMicrococcus luteus

Abstract: Infection structures were observed at the penetration sites on the leaves of cucumber plants inoculated with Colletotrichum orbiculare using a fluorescence microscope. The cucumber plants were previously drenched with suspension of bacterial strains Pseudomonas putida or Micrococcus luteus. The plants pre-inoculated with both bacterial strains were resistant against anthracnose after inoculation with C. orbiculare. To investigate the resistance mechanism by both bacterial strains, the surface of infected leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Generally, callose formed in host cells indicates a defense response against fungal invasion [28]. Callose, also known as “papillae” forming on host secondary cell wall, may play a role as barriers during early infection stages of the pathogen [29].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, callose formed in host cells indicates a defense response against fungal invasion [28]. Callose, also known as “papillae” forming on host secondary cell wall, may play a role as barriers during early infection stages of the pathogen [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an abundance of Micrococcus luteus has been reported in the ISI sample. Micrococcus luteus is a gram-positive bacterium that has been reported to exhibit antifungal activity 42 , 43 and its growth promoting properties, biocontrol properties 44 , biotic and abiotic stress tolerance 43 . Another study has reported the growth promoting properties of Micrococcus luteus against F.oxysporum in chickpea 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescent compounds often have rigid structures common to phenolic compounds involved in defence responses (Nicholson and Hammerschmidt, 1992;Davidson, 1996). Auto-fluorescence has been observed in other pathosystems and has been attributed to phytoalexin, amino acids, flavonoids, callose, and phenolic acids (Nicholson, 1977;Nicholson and Hammerschmidt, 1992;Dai et al, 1996;Jeun and Lee, 2005). In lettuce leaves infected with downy mildew, auto-fluorescence was attributed to the accumulation of ester-linked syringaldehyde and caffeic acid on plant cell walls, as well as the release of preformed phenolics from the vacuole in the HR (Bennett et al, 1996).…”
Section: Discussionmentioning
confidence: 99%